48.4k views
5 votes
Hey can you please help me posted picture of question

Hey can you please help me posted picture of question-example-1
User Sandro L
by
6.0k points

2 Answers

3 votes
The correct Option is (A) (x-1)(x-3)(x-5)

Step-by-step explanation:
As you can see in the graph that the graph intersects the x-axis at 3 points which are:

x = 1;
x = 3;
x = 5.

So the correct polynomial product is:
(x-1)(x-3)(x-5)

Because if we put them equals to zero we would get:
x-1=0
=> x=1

x-3 = 0
=> x = 3

x-5 = 0
=> x = 5(same as stated above)

Hence the correct option is (A) (x-1)(x-3)(x-5)
User Klobucar
by
5.9k points
0 votes
If we observe the graph we can see that the curve crosses the x-axis at the following points: 1, 3, and 5
This means x = 1, x = 3 and x = 5 are the roots of the polynomial and x - 1, x - 3 and x - 5 are the factors of the polynomial.

We can express the polynomial as the product of its factors. So the polynomial will be (x-1)(x-3)(x-5)

The correct answer to this question is option A

User Angely
by
6.3k points